DILEMA PERS BIROKRATIK DI ERA DEMOKRATISASI STUDI KASUS TABLOID KOMUNIKA KEMENTERIAN KOMUNIKASI DAN INFORMATIKA - Nursodik Gunarjo; Y.A. Nunung Prajarto; Ageng Setiawan Herianto (Jurnal Kawistara, 2013)
This study aims to analyze the dilemma in the bureaucratic press Tabloid Komunika (TK) of the Ministry of Communication and Information Technology of the Republic of Indonesia. TK chosen as the study site because it was published by government institution formerly known as Ministry of Information, which very repressive to the press in New Order era. The study uses case study approach reinforced by survey and content analysis methods. From the results of the study found, most graphic indicator of the freedom of journalists, public sphere openess, and the determination of the content, showed a random trend, while the freedom of access and opportunity of expression showed a rising trend. Inconsistencies in the implementation of elements of press democracy showed the dilemma in TK. Factors causing a dilemma in TK are: inconsistent leadership, unclear structure and functions of TK’s organization, and uncertainty management attitude. Bureaucratic power pressure lead TK’s organizers confused to divide partisanship to the community or the government. Dilemma in TK causes ambiguous contents, more actualized public opinion but the tone of articles are neutral toward the government.